Learning Interest and Writing Skills Among Madrasah Tsanawiyah Students: Theoretical and Empirical Perspectives - Muhammad Ridwan; Rusdi; Masrun; Randy Andeska (Assuthur: Jurnal Pendidikan Bahasa Arab, 2026)
This study was motivated by the low level of Arabic writing skills (maharah kitabah) among students, characterised by errors in letter formation and word linking, as well as low participation in writing activities. The aim of this study is to analyse the relationship between students’ interest in learning and their Arabic writing skills, and to identify the strength of the relationship between these two variables. The study employed a quantitative approach of a correlational nature. The study population consisted of 40 Year 8 students at MTs An-Nur Hangtuah Kampar, Riau, with a sample of 39 students. Data were collected via a learning interest questionnaire and a writing skills test, then analysed using descriptive statistics and Pearson’s correlation test with the aid of SPSS. The results of the study indicate that students’ learning interest falls into the ‘good’ category (mean = 77.21), whilst writing skills fall into the ‘low’ category (mean = 55.26). The correlation test yielded a value of r = 0.065 with a significance level of 0.695 (p > 0.05), indicating no significant relationship. These findings suggest that writing skills are influenced not only by learning interest but also by other factors such as vocabulary mastery, language rules, practice intensity, and teaching methods.